Fermentation of dry- and wet-extruded pea protein texturates for flavor development - Maurice König; Marina Rigling; Yanyan Zhang; Myriam Loeffler; Jochen Weiss (International Journal of Food Microbiology, 2026)

Influence of residual pressure on color stability of vacuum packaged beef - Johannes Krell; Theresa Müller; Alejandro Poveda-Arteaga; Jochen Weiss; Nino Terjung; Monika Gibis (Innovative Food Science & Emerging Technologies, 2026)

Encapsulation of curcumin by hetero-protein aggregates of whey protein isolate and lysozyme - Lorena Avila Cortes; Jochen Weiss; Monika Gibis (Innovative Food Science & Emerging Technologies, 2026)

Post-translational modifications of proteins and their effect on techno-functional properties for food applications - Theresa Scheuerer; Eva Herz; Sathaporn Srichuwong; Jochen Weiss (Critical Reviews in Food Science and Nutrition, 2026)

Preparation of electrospun fibers from aqueous lysozyme and maltodextrin blends and fiber morphology - Monika Gibis; Heiko Rumig; Jochen Weiss; Till Schumacher (Food Hydrocolloids, 2026)

Interfacial properties of dry-fractionated lentil protein concentrates and their water-extracted soluble and insoluble fractions as affected by pH - Matthias Funke; Zsofia Megmondja; Remko Boom; Jochen Weiss (Food Research International, 2026)

Impact of xanthan gum/locust bean gum complex and oil types on rheological properties and sensory attributes of gel-in-oil-in-water (G/O/W) double emulsion - Jaehyun Jeong; Jiwon Kwon; Jiseon Lee; Jochen Weiss; Mi-Jung Choi (Food Hydrocolloids, 2025)

Enhancing the stability of xanthan/locust bean gum–based double emulsions using canola and medium-chain triglyceride oils: Examination of physicochemical and thermal properties - Jaehyun Jeong; Jiwon Kwon; Jiseon Lee; Jochen Weiss; Mi-Jung Choi (Food Chemistry, 2025)

Structural changes of complexes from Arthrospira platensis protein and pectin influenced by degree of esterification and pH - Stephan Buecker; Monika Gibis; Laura Bartmann; Sara Bussler; Jochen Weiss (Food Hydrocolloids, 2025)

Fish Assemblage Characteristics and Allochthonous Food Resources Shape the Topology of Trophic Networks in Blackwater Floodplain Forests - Bianca Weiss; Fernanda Costa; Flavia Santana; Viviane Pagnussat Klein; Aline Lopes; Gilvan Costa; Jochen Schöngart; Florian Wittmann; Flavia Durgante; Jansen Zuanon; Maria Teresa Fernandez Piedade (Wetlands, 2025)

Physico-chemical characterization of ten commercial pea protein isolates - Till Schumacher; Tatjana Steinmacher; Elena Köster; Anja Wagemans; Jochen Weiss; Monika Gibis (Food Hydrocolloids, 2025)

Study of interactive forces and complex formation from Arthrospira platensis extract with high methoxylated pectin, low methoxylated pectin and lambda-carrageenan - Stephan Buecker; Elena Leeb; Monika Gibis; Jochen Weiss (Food Hydrocolloids, 2025)

Effect of air volume flow rates on pyrolysis temperatures and flue gas compositions to control smoldering smoke generation - Malte Leible; Carlos Woern; Kurt Herrmann; Monika Gibis; Jochen Weiss (Journal of Food Engineering, 2025)

Uncovering the light absorption mechanism of the blue natural colorant allophycocyanin from Arthrospira platensis using molecular dynamics - Stephan Buecker; Jeffrey M. Sanders; Paul Winget; Elena Leeb; Lutz Grossmann; Monika Gibis; Jochen Weiss (Food Chemistry, 2025)

Stability of anthocyanin extracts from chokeberry, grape, hibiscus, and purple sweet potato in ω-3-fatty acid rich oil-in-water emulsions - Evelyn Klinger; Hanna Salminen; Karola Bause; Jochen Weiss (Food Chemistry, 2024)

Modelling of dynamic mastication physics of cheese/casein gels as function of milk-fat distribution and intensity of thermo-mechanical treatment - Dominic Oppen; Florian Schmidt; Sarah Helena Braitmaier; Jörg Hinrichs; Jochen Weiss (Food Research International, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Effects of potential key substances in woodchips smoldering smoke on the formation of heterocyclic amines and polycyclic aromatic hydrocarbons in Frankfurter sausages - Yi-qun Cheng; Malte Leible; Marina Rigling; Jochen Weiss; Yan-yan Zhang; Monika Gibis (Food Research International, 2024)

Cold gelation of canola protein isolate and canola protein hydrolysates - Nicola Lea Lerch; Amir Vahedifar; Jochen Weiss; Jianping Wu (Food Hydrocolloids, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Insights into characterizing and producing anisotropic food structures - Dominic Oppen; Lutz Grossmann; Jochen Weiss (Critical Reviews in Food Science and Nutrition, 2024)

Anticipating food structure of meat products from mastication physics applying machine learning - Dominic Oppen; Tabea Attig; Jochen Weiss; Christian Krupitzer (Food Research International, 2023)

A review on the relation between grinding process and quality of ground meat - Lisa M. Berger; Franziska Witte; Igor Tomasevic; Volker Heinz; Jochen Weiss; Monika Gibis; Nino Terjung (Meat Science, 2023)

The impact of temperature-controlled smoldering smoking on polycyclic aromatic hydrocarbons and heterocyclic amines contents in Frankfurter-type sausages - Yi-qun Cheng; Malte Leible; Jochen Weiss; Monika Gibis (Food Chemistry, 2023)

Effect of manufacturing and frozen meat temperatures on structural and functional properties of hamburgers - Lisa M. Berger; Carsten Böckle; Monika Gibis; Kurt Herrmann; Nino Terjung; Jochen Weiss (Journal of Food Engineering, 2023)

Homogenization increases stickiness of concentrated pea protein - apple pectin mixtures - Pascal Moll; Hanna Salminen; Miriam Spengler; Christophe Schmitt; Jochen Weiss (Journal of Food Engineering, 2023)

Fibrous food and particle size influence electromyography and the kinematics of oral processing - Dominic Oppen; Ashley K. Young; Hans-Peter Piepho; Jochen Weiss (Food Research International, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Issues surrounding consumer trust and acceptance of existing and emerging food processing technologies - Gert W. Meijer; Liisa Lähteenmäki; Richard H. Stadler; Jochen Weiss (Critical Reviews in Food Science and Nutrition, 2021)

Cultivation and downstream processing of microalgae and cyanobacteria to generate protein-based technofunctional food ingredients - Lutz Grossmann; Jörg Hinrichs; Jochen Weiss (Critical Reviews in Food Science and Nutrition, 2020)

Recent advances in cured raw ham manufacture - Ramona Bosse (née Danz); Anne Müller; Monika Gibis; Agnes Weiss; Herbert Schmidt; Jochen Weiss (Critical Reviews in Food Science and Nutrition, 2018)

What Makes Good Antioxidants in Lipid-Based Systems? The Next Theories Beyond the Polar Paradox - Mickaël Laguerre; Christelle Bayrasy; Atikorn Panya; Jochen Weiss; D. Julian McClements; Jérôme Lecomte; Eric A. Decker; Pierre Villeneuve (Critical Reviews in Food Science and Nutrition, 2015)

Effects of induced fatigue on brain activity during sensorimotor control - Jochen Baumeister; Kirsten Reinecke; Michael Schubert; Johannes Schade; Michael Weiss (European Journal of Applied Physiology, 2012)

Factors Influencing the Chemical Stability of Carotenoids in Foods - Caitlin S. Boon; D. Julian McClements; Jochen Weiss; Eric A. Decker (Critical Reviews in Food Science and Nutrition, 2010)

Structural Design Principles for Delivery of Bioactive Components in Nutraceuticals and Functional Foods - David Julian McClements; Eric Andrew Decker; Yeonhwa Park; Jochen Weiss (Critical Reviews in Food Science and Nutrition, 2009)

Cortical activity of skilled performance in a complex sports related motor task - Jochen Baumeister; Kirsten Reinecke; Heinz Liesen; Michael Weiss (European Journal of Applied Physiology, 2008)